A new family of mathematical models describing the human growth curve—Erratum: Direct calculation of peak height velocity, age at take-off and associated quantities. (May 2013) - Sayers, Adrian; Baines, Mike; Tilling, Kate
<x xml:space="preserve">Abstract</x> A new family of mathematical functions to fit longitudinal growth data was described in 1978. The ability of researchers to directly use parameters as estimates of age at peak height velocity resulted in them overlooking the possibility of directly calculating these quantities after model estimation. This erratum has corrected three mistakes in the original manuscript in the direct calculation of peak height velocity and age at take-off and has implemented the solutions in a STATA program which directly calculates the estimates, standard errors and confidence intervals for age, height and velocity at peak height velocity.